LIFE SAVING IS COST EFFECTIVE - DENTAL PULP STEM CELLS - K.M.K.MASTHAN; N.ARAVINDHA BABU; S.LEENA SANKARI; T.GOPALA KRISNAN; M.ELUMALAI (International Journal of Pharma and Bio Sciences, 2013)
Stem cells are biological cells found in all multicellular organisms that can divide and differentiate into diverse specialized cell types and can self renew to produce more stem cells.However, the knowledge in stem cell technology is increasing quickly in all medical specialties and in dental field too. The applications of stem cells are to cure diseases like juvenile diabetes, Parkinson’s, spinal injuries certain forms of cancer and heart problems. Various researches are undergoing to use the stem cells for curing other diseases also. The aim of this paper is to review the economy behind the stem cell banking and to highlight how dental pulp stem cells are cost-effective.